2011
DOI: 10.3348/kjr.2011.12.1.15
|View full text |Cite|
|
Sign up to set email alerts
|

Diffusion and Perfusion Characteristics of MELAS (Mitochondrial Myopathy, Encephalopathy, Lactic Acidosis, and Stroke-Like Episode) in Thirteen Patients

Abstract: ObjectiveWe analyzed the diffusion and perfusion characteristics of acute MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episode) lesions in a large series to investigate the controversial changes of the apparent diffusion coefficient (ADC) that were reported in prior studies.Materials and MethodsWe analyzed 44 newly appearing lesions during 28 stroke-like episodes in 13 patients with MELAS. We performed a visual assessment of the MR images including the ADC and perfusion maps,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
73
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 24 publications
(26 reference statements)
3
73
0
1
Order By: Relevance
“…Many studies have shown almost consistent results regarding the perfusion status around the time of a stroke: i.e., hyperperfusion in the acute stage followed by hypoperfusion in the subacute and chronic stages [9,11,16,[20][21]. Our study revealed similar lesion-associated chronological changes in CBF.…”
Section: Discussionsupporting
confidence: 84%
“…Many studies have shown almost consistent results regarding the perfusion status around the time of a stroke: i.e., hyperperfusion in the acute stage followed by hypoperfusion in the subacute and chronic stages [9,11,16,[20][21]. Our study revealed similar lesion-associated chronological changes in CBF.…”
Section: Discussionsupporting
confidence: 84%
“…Concerning the possible role of seizures and/or SLE treatment in the arterial abnormalities reported, in our opinion, this seems unlikely, since two of the three patients lacked clinical and EEG abnormalities in favor of epilepsy, and arterial abnormalities were restricted to the brain areas involved by the SLE. One might suspect a more diffuse cerebral artery dilatation in treatment-induced perfusion abnormalities, although an interaction between SLE treatment therapies and cerebral arteries only involved in the SLE cannot be excluded.The variability of signal changes on ADC map in SLE in our three patients corresponded well to the earlier reports analyzing ADC in SLE showing cortical hypo-, iso-, or hyperintensities during SLE, probably also depending on the timing of MRI performance (and the stage of SLE) [1,2]. …”
supporting
confidence: 75%
“…The variability of signal changes on ADC map in SLE in our three patients corresponded well to the earlier reports analyzing ADC in SLE showing cortical hypo-, iso-, or hyperintensities during SLE, probably also depending on the timing of MRI performance (and the stage of SLE) [1,2].…”
supporting
confidence: 75%
“…Global atrophy and calcification of the basal ganglia are sometimes present [16]. MRI characteristically shows hyperintensity on diffusion weighted imaging and FLAIR with a predilection for the parietal, temporal, and occipital cortex, without conforming to a single vascular territory, a hallmark finding of MELAS [19], [20], [21]. Blood vessels typically are normal on angiographic evaluation, although cases of vasoconstriction have been reported [22].…”
Section: Discussionmentioning
confidence: 99%